Strengthening national salt reduction strategies using multiple methods process evaluations: case studies from Malaysia and Mongolia - Briar L McKenzie; Feisul Idzwan Mustapha; Bat-Erdene Battumur; Enkhtungalag Batsaikhan; Arunah Chandran; Viola Michael; Jacqui Webster; Kathy Trieu (Cambridge University Press, 2024)
Abstract Objective: To understand the extent to which national salt reduction strategies in Malaysia and Mongolia were implemented and achieving their intended outcomes. Design: Multiple methods process evaluations conducted at the mid-point of strategy implementation, guided by theoretical frameworks. Setting: Malaysia (2018-2019) and Mongolia (2020-2021). Participants: Desk-based reviews of related documents, interviews with key stakeholders (n 12 Malaysia, n 10 Mongolia), focus group discussions with health professionals in Malaysia (n 43) and health provider surveys in Mongolia (n 12). Results: Both countries generated high-quality local evidence about salt intake and levels in foods and culturally specific education resources. In Malaysia, education and reformulation activities were delivered with moderate dose (quantity) but reach among the population was low. Within 5 years, Mongolia implemented education among schools, health professionals and food producers on salt reduction with high reach, but with moderate dose (quantity) and reach among the general population. Both countries faced challenges in implementing legislative interventions (mandatory salt labelling and salt limits in packaged foods) and both could improve the scaling up of their reformulation and education activities. Conclusions: In the first half of Malaysia's and Mongolia's strategies, both countries generated necessary evidence and education materials, mobilised health professionals to deliver salt reduction education and achieved small-scale reformulation in foods. Both subsequently should focus on implementing regulatory policies and achieving population-wide reach and impact. Process evaluations of existing salt reduction strategies can help strengthen intervention delivery, aiding achievement of WHO's 30 % reduction in salt intake by 2025 target.